Strategi Pengembangan Program Kawasan Rumah Pangan Lestari (KRPL) pada Kelompok Wanita Tani Karya Harum di Desa Karang Sidemen, Lombok Tengah - ASKINA, BAIQ RIA; WINDIA, I WAYAN; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.3, Juli 2017DO - 10.24843/JAA.2017.v06.i03.p01, 2017)
Region Development Strategy for Sustainable Food Houses Program (KRPL) on Women Farmers Group Karya Harum Village of Karang Sidemen Central Lombok Regency KRPL program is the concept of optimizing the use of yard area with a variety of crops, livestock and fish in one area.The research objective was to determine the internal and external factors and determine the development strategy KRPL program in the village of Karang Sidemen.The results of the analysis of internal factors Karya Harum group: a) the power (the availability of nurseries and mastery of technology is the most influential factor) b) weakness (the education background of KWT management is still a major factor of group weakness). External factors: a) the opportunities (the presence of a certain partner is an important factor) b) threats (the weather conditions are a threat within KRPL program development).Based on SWOT analysis, there are development strategies: a) SO strategy that is revitalizing the village seedlings (KBD) and strategy to maintain the partners, b) WO strategy is the strategy of increasing the quantity of cultivation of plants and training strategy of product development of the product of the yard, c)ST strategy namely water and hydroponics harvesting technology extension strategies to the group, d) WT strategy is stimulant strategy. Priority of strategy can be done by reviving the KBD and maintaining partners.